C.
She said that I don’t need her 54
Simplifying
10 + 5x = 5x + 10
Reorder the terms:
10 + 5x = 10 + 5x
Add '-10' to each side of the equation.
10 + -10 + 5x = 10 + -10 + 5x
Combine like terms: 10 + -10 = 0
0 + 5x = 10 + -10 + 5x
5x = 10 + -10 + 5x
Combine like terms: 10 + -10 = 0
5x = 0 + 5x
5x = 5x
Add '-5x' to each side of the equation.
5x + -5x = 5x + -5x
Combine like terms: 5x + -5x = 0
0 = 5x + -5x
Combine like terms: 5x + -5x = 0
0 = 0
Solving
0 = 0
Answer: 0 solutions
Answer:
The equation of this line would be y = 11x - 48
Step-by-step explanation:
To get this equation, we first have to find the slope. We do that with the slope eqaution.
m(slope) = (y2 - y1)/(x2 - x1)
m = (-4 - 7)/(4 - 5)
m = -11/-1
m = 11
Now we can use this slope and either point in point-slope form to find the equation.
y - y1 = m(x - x1)
y - 7 = 11(x - 5)
y - 7 = 11x - 55
y = 11x - 48
Answer:
x=-13/9
Step-by-step explanation:
8/9=x+7/3
8/9-7/3=x
8/9-(3)7/9=x
8/9-21/9=x
-13/9=x
I hope this helped. If you have any questions, please feel free to ask them.
Answer:
12/16, 6/8, 15/20, 24/32
Step-by-step explanation:
Because to find the equivalents, you have to multiply/ divide the numerator and the denominator with the same number.